High-valued comprehensive utilization method of waste battery diaphragm

By catalyzed pyrolysis and oxidation treatment of waste battery separators and titanium dioxide waste acid, the problem of waste battery separators and titanium dioxide waste acid treatment is solved, and the high-value utilization of resources and environmental protection is achieved.

CN119390097APending Publication Date: 2025-02-07NORTH CHINA ELECTRIC POWER UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411542371.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The prior art cannot efficiently handle waste battery separators and titanium dioxide waste acid, resulting in waste of resources and environmental pollution.

Method used

Aromas and porous alumina are prepared by mixing the waste battery separator with titanium dioxide waste acid for catalytic pyrolysis, and polymerized aluminum sulfate flocculant is prepared by oxidation, polymerization and maturation of the titanium dioxide waste acid.

Benefits of technology

The high-value utilization of waste battery separators and titanium dioxide waste acid was realized, high-value aromatic hydrocarbons and porous alumina were prepared, and polymeric aluminum sulfate flocculant with water purification effect was prepared, which promoted the recycling of resources and the environment. protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005113078460000111
    Figure BDA0005113078460000111
  • Figure BDA0005113078460000121
    Figure BDA0005113078460000121
Patent Text Reader

Abstract

The invention discloses a high-valued comprehensive utilization method of a waste battery diaphragm. The method comprises the following steps: S1, mixing and filtering the waste battery diaphragm and titanium white waste acid to obtain filtrate and a pretreated battery diaphragm in which part of an aluminum oxide coating is removed; wherein the pretreated battery diaphragm is subjected to catalytic pyrolysis, and aromatic hydrocarbon and solid carbon are obtained; s2, the filtrate is subjected to oxidation, polymerization and curing in sequence, and polyaluminum ferric sulfate is obtained.By means of the method, the waste battery diaphragm can be efficiently recycled, and titanium dioxide waste acid is fully purified and utilized. The method can realize selective preparation of aromatic hydrocarbon by catalytic pyrolysis of the waste battery diaphragm, can also comprehensively utilize the main component ferrous sulfate of the titanium dioxide waste acid to obtain polyaluminum ferric sulfate, can also obtain the coating material aluminum oxide of the waste battery diaphragm, and is a feasible and efficient method for realizing high-value utilization of the waste battery diaphragm and the titanium dioxide waste acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of organic waste utilization, and specifically relates to a method for high-value comprehensive utilization of waste battery separators. Background Art

[0002] In recent years, the new energy vehicle industry has developed rapidly. Batteries are the core components of new energy vehicles, and their design life is generally 6 to 10 years. Currently, a large number of batteries are on the verge of retirement. Batteries are usually composed of positive electrodes, negative electrodes, electrolytes and separators. Among them, the separator, as an indispensable component of the battery, determines the number of cycles, cost and safety of the battery. The separator is mainly composed of polyethylene (PE) or polypropylene (PP), and an inorganic coating is used to improve the thermal stability of the separator and its affinity for the electrolyte. Commonly used inorganic coating materials include alumina, silica, etc. At present, alumina-coated separators have been commercialized in the field of new energy vehicles. It is estimated that by 2030, the cumulative amount of waste battery separators will reach 5 billion square meters. At present, the disposal methods of waste battery separators mainly include incineration and landfill. However, these technologies have disadvantages such as low efficiency and serious pollution. Therefore, it is urgent to find a green and efficient waste battery separator disposal technology.

[0003] Titanium dioxide waste acid is the waste acid produced in the production process of titanium dioxide. In addition to sulfuric acid, the main component of titanium dioxide waste acid, there are about 25% ferrous sulfate. If titanium dioxide waste acid is discharged directly without treatment, it will not only pollute the environment, but also cause serious waste of resources. At present, in domestic titanium dioxide enterprises, the industrial application of titanium dioxide waste acid treatment methods mainly include vacuum concentration, lime neutralization, and leaching phosphate ore to produce phosphoric acid. Vacuum concentration has high requirements for equipment and high costs. Lime neutralization produces more by-products, which are difficult to handle later. Leaching phosphate ore to produce phosphoric acid only transfers the pollution problem in the early stage to the process of preparing phosphoric acid in the later stage, and the later treatment is still quite severe. How to deal with these waste acids and economically and reasonably recover the valuable parts has become an important technical problem in the production of titanium dioxide by sulfuric acid, and it is also a major problem that plagues environmental protection and the development of the titanium dioxide industry.

[0004] Therefore, it is of great practical significance to develop a process that can not only efficiently treat waste battery separators but also purify waste titanium dioxide acid. Summary of the invention

[0005] The present invention aims at the problem that the existing waste battery diaphragm treatment method cannot fully realize waste utilization, and the waste titanium dioxide acid cannot be fully purified and recycled or the recycling cost is high. The present invention provides a new high-value comprehensive utilization method for waste battery diaphragms. The method can efficiently recycle waste battery diaphragms and fully purify and utilize waste titanium dioxide acid. It can not only realize the selective preparation of aromatics by catalytic pyrolysis of waste battery diaphragms, but also comprehensively utilize ferrous sulfate, the main component of waste titanium dioxide acid, and purify waste titanium dioxide acid. It can also obtain aluminum oxide, a coating material for waste battery diaphragms. It is a feasible and efficient method for realizing high-value utilization of waste battery diaphragms and waste titanium dioxide acid, and realizing green development.

[0006] In order to solve the above technical problems, the present invention provides a method for high-value comprehensive utilization of waste battery separators, comprising the following steps:

[0007] S1, mixing and filtering the waste battery separator and titanium dioxide waste acid to obtain a filtrate and a pretreated battery separator with a portion of the aluminum oxide coating removed; wherein the pretreated battery separator is subjected to catalytic pyrolysis to obtain aromatic hydrocarbons and solid carbon;

[0008] S2, oxidizing, polymerizing and aging the filtrate in sequence to obtain polyaluminium ferric sulfate.

[0009] In the present invention, the waste battery separator may be a waste lithium-ion battery separator, etc., and is mainly aimed at waste battery separators with aluminum oxide coatings.

[0010] According to some embodiments of the present invention, in S1, the amounts of waste battery separator and titanium dioxide waste acid satisfy a solid-liquid ratio of 1: (10-20) g / mL.

[0011] According to some embodiments of the present invention, the mixing conditions include: a temperature of 90 to 110° C. and a time of 2 to 5 hours.

[0012] According to some embodiments of the present invention, preferably, washing and drying are performed after the filtering; more preferably, the drying conditions include: a temperature of 80 to 120° C. and a time of 6 to 24 hours.

[0013] According to some embodiments of the present invention, the waste battery separator is a battery separator having an aluminum oxide coating.

[0014] According to some embodiments of the present invention, the titanium dioxide waste acid is waste acid generated during the production of titanium dioxide, and the titanium dioxide waste acid contains about 25% ferrous sulfate in addition to sulfuric acid as a main component. In the present invention, the titanium dioxide waste acid can be conventional titanium dioxide waste acid in the art.

[0015] According to some embodiments of the present invention, the weight of aluminum oxide in the pretreated battery separator is reduced by 10 to 40 wt% relative to the waste battery separator. In the present invention, partial removal of the aluminum oxide coating refers to removing a portion of the aluminum oxide coating of the separator by pretreatment with titanium dioxide waste acid, so that the aluminum oxide coating in the separator is reduced by 10 to 40 wt%.

[0016] According to some embodiments of the present invention, the catalyst for the catalytic pyrolysis is HZSM-5. Pyrolysis is a green and efficient thermal conversion technology, especially under the action of appropriate catalysts, it can quickly convert organic matter into fuels rich in specific high value-added compounds, such as aromatics. Aromatics are a class of hydrocarbons with a stable aromatic ring structure, which have special aroma and chemical properties and are widely used in the fields of chemical industry, medicine, etc. HZSM-5 has high catalytic performance in the preparation of aromatics by catalytic pyrolysis due to its strong acidity, high thermal stability and unique pore structure. HZSM-5 contains rich B acid sites and a unique MFI-type pore structure, which can effectively promote reactions such as cracking, hydrogen transfer, cyclization and aromatization of polymer pyrolysis volatiles, thereby promoting the formation of aromatics.

[0017] According to some embodiments of the present invention, the amount of catalyst used in the catalytic pyrolysis is catalyst:pretreated battery separator=(4-12):1.

[0018] According to some embodiments of the present invention, the conditions for the catalytic pyrolysis include: a temperature of 500 to 700° C. and a time of 10 to 20 min.

[0019] According to some embodiments of the present invention, in S1, after catalytic pyrolysis, volatile components are obtained and condensed to obtain aromatic hydrocarbons. In the present invention, the condensation temperature is preferably 0-4°C.

[0020] According to some embodiments of the present invention, the oxidant used in the oxidation is hydrogen peroxide. Preferably, the weight ratio of the filtrate to the hydrogen peroxide is (10-20):1.

[0021] According to some embodiments of the present invention, the oxidation conditions include stirring until the solution is yellow-brown. According to some embodiments of the present invention, the polymerization conditions include: temperature of 70-80°C, stirring speed of 200-400 r / min, and time of 2-5 h.

[0022] According to some embodiments of the present invention, the aging conditions include: reacting at a temperature of 70 to 80° C. and a stirring speed of 200 to 400 r / min for 24 to 48 hours.

[0023] According to some embodiments of the present invention, preferably, the solid carbon is calcined to obtain porous alumina; preferably, the calcination conditions include: a temperature of 400 to 500° C. and a time of 1 to 2 hours.

[0024] Beneficial effects of the present invention:

[0025] (1) The present invention can achieve high-value and clean utilization of waste battery diaphragms and waste titanium dioxide acid: the organic components in the diaphragm are catalytically pyrolyzed to produce high-value aromatic hydrocarbons, which can be used as hydrogen storage liquid fuel or chemicals, while the pyrolysis solid products are recovered to form porous alumina; the waste titanium dioxide acid can be further prepared into polyaluminum ferric sulfate flocculant.

[0026] (2) The present invention innovatively proposes a new method for selectively preparing aromatics by limited removal of inorganic components of the diaphragm and enhanced catalytic pyrolysis. The limited removal of the alumina coating of the diaphragm by titanium dioxide waste acid can not only effectively reduce the heat and mass transfer resistance during the pyrolysis of the diaphragm and promote the pyrolysis and volatilization of organic components, but also strengthen the contact between the volatile matter and alumina, give full play to the catalytic function of alumina, promote the decomposition of macromolecular substances into more small molecular olefins, and facilitate the subsequent cyclization, aromatization and other reactions under the action of the HZSM-5 catalyst, while increasing the yield of aromatics and reducing the coking and deactivation of the catalyst surface.

[0027] (3) Polyaluminium ferric sulfate is a new type of inorganic polymer flocculant, which has both the water purification effect of aluminium salt and the decolorization effect of iron salt, and has low water treatment cost. At the same time, it overcomes the shortcomings of high cost of pure aluminium salt, excessive aluminium residue in water that is harmful to the environment, and yellowing and blackening of pure iron salt, excessive iron ions, and inability to be recycled by printing and dyeing enterprises. Existing polyaluminium ferric sulfate is mostly prepared by traditional preparation methods, such as using sodium nitrite as a catalyst to accelerate the reaction speed, and generating NOx gas that has an impact on the environment during the preparation process. At the same time, traditional processes mostly use industrial-grade green vitriol or materials containing iron, aluminium, etc. as raw materials, which have high requirements for raw materials and high production costs. The present invention proposes a new method for efficiently preparing polyaluminium ferric sulfate flocculant from titanium dioxide waste acid. Titanium dioxide waste acid contains a large amount of acidic substances, and a large amount of alkaline reagents are required for neutralization during conventional disposal. The present invention uses it to react with inorganic components in the diaphragm, reducing the consumption of alkaline reagents. The filtrate after membrane pretreatment is rich in ferrous sulfate, which can be oxidized into ferric sulfate by adding hydrogen peroxide. At the same time, the aluminum oxide dissolved during pretreatment will form aluminum sulfate. After the ferric sulfate and aluminum sulfate are polymerized and matured, polyaluminum ferric sulfate flocculant is obtained. Polyaluminum ferric sulfate has the advantages of large molecular structure, strong adsorption capacity, good water purification effect, fast precipitation speed, and wide applicable pH range. It is now widely used in the turbidity removal of various industrial water and the treatment of industrial wastewater such as mining, printing and dyeing, papermaking, food, and leather. DETAILED DESCRIPTION

[0028] The present invention provides a method for high-value utilization of waste battery separators, and the present invention is further described below in conjunction with specific embodiments. It should be understood that the following specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0029] The calculation method of the liquid product yield in the following examples is as follows:

[0030] Liquid product yield = (mass of collected liquid product / mass of raw material) × 100%.

[0031] In the following examples, the content of aromatics in the liquid product was analyzed by gas chromatography / mass spectrometry and quantified by external standard method. The calculation method of the aromatics yield is as follows:

[0032] Yield of aromatic hydrocarbons = (mass of aromatic hydrocarbons / mass of raw materials) × 100%.

[0033] The percentages in the following examples are by mass unless otherwise specified.

[0034] Example 1

[0035] Take an appropriate amount of waste battery separator and immerse it in titanium dioxide waste acid at a solid-liquid ratio of 1:10 (g / mL), stir it at 90°C for 2h, then filter it, wash the filter residue with deionized water until it is neutral, and finally dry it at 80°C for 6h to obtain the filtrate and the pretreated battery separator. It was measured that the weight of aluminum oxide in the aluminum oxide coating of the pretreated battery separator decreased by 31wt%.

[0036] Take an appropriate amount of the above-pretreated battery separator and HZSM-5 catalyst, mechanically mix them according to HZSM-5 / raw material = 4:1, and quickly pyrolyze them at 500℃ for 20min to obtain volatile components and solid carbon. The volatile components are condensed at 0℃ to obtain a liquid product with a liquid product yield of 56.23%. The content of aromatics therein is analyzed by gas chromatography, and the yield of aromatics is calculated to be 44.14%. The pyrolyzed solid carbon is calcined at 400℃ for 1h to obtain porous alumina. It was determined that the average particle size of the porous alumina is 57nm and the specific surface area is 257m 2 / g, pore volume is 0.485cm 3 / g.

[0037] Take an appropriate amount of the pretreated filtrate, add hydrogen peroxide to the filtrate, the weight ratio of the filtrate to hydrogen peroxide is 13:1, and stir until the solution is yellow-brown. Then control the polymerization stirring speed to 200r / min, the water bath temperature to 70°C, and the time to 2h. Then control the aging stirring speed to 200r / min, the water bath temperature to 70°C, and the time to 24h, and finally obtain liquid polyaluminum ferric sulfate.

[0038] Example 2

[0039] Take an appropriate amount of waste battery separator and immerse it in titanium dioxide waste acid at a solid-liquid ratio of 1:20 (g / mL), stir it at 90°C for 2h, then filter it, wash the filter residue with deionized water until it is neutral, and finally dry it at 120°C for 16h to obtain the filtrate and the pretreated battery separator. It was measured that the weight of aluminum oxide in the aluminum oxide coating of the pretreated battery separator decreased by 10wt%.

[0040] Take an appropriate amount of the above-pretreated battery separator and HZSM-5 catalyst, mechanically mix them according to HZSM-5 / raw material = 4:1, and quickly pyrolyze them at 550°C for 18 minutes to obtain volatile components and solid carbon. The volatile components are condensed at 0°C to obtain a liquid product with a liquid product yield of 50.33%. The content of aromatics therein is analyzed by gas chromatography, and the yield of aromatics is calculated to be 40.04%. The pyrolyzed solid carbon is calcined at 400°C for 2 hours to obtain porous alumina. It was determined that the average particle size of the porous alumina was 64nm and the specific surface area was 563m 2 / g, pore volume is 0.636cm 3 / g.

[0041] Take an appropriate amount of the pretreated filtrate, add hydrogen peroxide to the filtrate, the weight ratio of the filtrate to hydrogen peroxide is 18:1, and stir until the solution is yellow-brown. Then control the polymerization stirring speed to 400r / min, the water bath temperature to 80°C, and the time to 5h. Then control the aging stirring speed to 400r / min, the water bath temperature to 80°C, and the time to 48h, and finally obtain liquid polyaluminum ferric sulfate.

[0042] Example 3

[0043] Take an appropriate amount of waste battery separator and immerse it in titanium dioxide waste acid at a solid-liquid ratio of 1:20 (g / mL), stir it at 110°C for 5h, then filter it, wash the filter residue with deionized water until it is neutral, and finally dry it at 120°C for 6h to obtain the filtrate and the pretreated battery separator. It was measured that the weight of aluminum oxide in the aluminum oxide coating of the pretreated battery separator decreased by 30wt%.

[0044] Take an appropriate amount of the above-pretreated battery separator and HZSM-5 catalyst, mechanically mix them according to HZSM-5 / raw material = 6:1, and quickly pyrolyze them at 650°C for 16 minutes to obtain volatile components and solid carbon. The volatile components are condensed at 2°C to obtain a liquid product with a liquid product yield of 53.43%. The content of aromatics therein is analyzed by gas chromatography, and the yield of aromatics is calculated to be 43.10%. The pyrolyzed solid carbon is calcined at 500°C for 2 hours to obtain porous alumina. It was determined that the average particle size of the porous alumina is 55nm and the specific surface area is 425m 2 / g, pore volume is 0.424cm 3 / g.

[0045] Take an appropriate amount of the pretreated filtrate, add hydrogen peroxide to the filtrate, the weight ratio of the filtrate to hydrogen peroxide is 14:1, and stir until the solution is yellow-brown. Then control the polymerization stirring speed to 250r / min, the water bath temperature to 80°C, and the time to 4h. Then control the aging stirring speed to 350r / min, the water bath temperature to 75°C, and the time to 36h, and finally obtain liquid polyaluminum ferric sulfate.

[0046] Example 4

[0047] Take an appropriate amount of waste battery separator and immerse it in titanium dioxide waste acid at a solid-liquid ratio of 1:17 (g / mL), stir it at 90℃ for 2h, then filter it, wash the filter residue with deionized water until it is neutral, and finally dry it at 110℃ for 19h to obtain the filtrate and the pretreated battery separator. It was measured that the weight of alumina in the alumina coating of the pretreated battery separator decreased by 36wt%.

[0048] Take an appropriate amount of the above-pretreated battery separator and HZSM-5 catalyst, mechanically mix them according to HZSM-5 / raw material = 6:1, and quickly pyrolyze them at 600℃ for 17 minutes to obtain volatile components and solid carbon. The volatile components are condensed at 3℃ to obtain a liquid product with a liquid product yield of 66.29%. The content of aromatics therein is analyzed by gas chromatography, and the yield of aromatics is calculated to be 58.13%. The pyrolyzed solid carbon is calcined at 400℃ for 1h to obtain porous alumina. It was determined that the average particle size of the porous alumina is 51nm and the specific surface area is 221m 2 / g, pore volume is 0.421cm 3 / g.

[0049] Take an appropriate amount of the pretreated filtrate, add hydrogen peroxide to the filtrate, the weight ratio of the filtrate to hydrogen peroxide is 18:1, and stir until the solution is yellow-brown. Then control the polymerization stirring speed to 220r / min, the water bath temperature to 76°C, and the time to 5h. Then control the aging stirring speed to 340r / r / min, the water bath temperature to 72°C, and the time to 29h, and finally obtain liquid polyaluminum ferric sulfate.

[0050] Example 5

[0051] Take an appropriate amount of waste battery separator and immerse it in titanium dioxide waste acid at a solid-liquid ratio of 1:14 (g / mL), stir it at 110℃ for 5h, then filter it, wash the filter residue with deionized water until it is neutral, and finally dry it at 120℃ for 24h to obtain the filtrate and the pretreated battery separator. It was measured that the weight of alumina in the alumina coating of the pretreated battery separator decreased by 34wt%.

[0052] Take an appropriate amount of the above-pretreated battery separator and HZSM-5 catalyst, mechanically mix them according to HZSM-5 / raw material = 6:1, and quickly pyrolyze them at 600°C for 15 minutes to obtain volatile components and solid carbon. The volatile components are condensed at 4°C to obtain a liquid product with a liquid product yield of 62.78%. The content of aromatics therein is analyzed by gas chromatography, and the yield of aromatics is calculated to be 52.45%. The pyrolyzed solid carbon is calcined at 400°C for 2 hours to obtain porous alumina. It was determined that the average particle size of the porous alumina is 59nm and the specific surface area is 248m 2 / g, pore volume is 0.499cm 3 / g.

[0053] Take an appropriate amount of the above pretreated filtrate, add hydrogen peroxide to the filtrate, the weight ratio of the filtrate to hydrogen peroxide is 15:1, and stir until the solution is yellow-brown. Then control the polymerization stirring speed to 320r / min, the water bath temperature to 80°C, and the time to 4h. Then control the aging stirring speed to 310r / min, the water bath temperature to 75°C, and the time to 24h, and finally obtain liquid polyaluminum ferric sulfate.

[0054] Example 6

[0055] Take an appropriate amount of waste battery separator and immerse it in titanium dioxide waste acid at a solid-liquid ratio of 1:13 (g / mL), stir it at 110℃ for 5h, then filter it, wash the filter residue with deionized water until it is neutral, and finally dry it at 110℃ for 21h to obtain the filtrate and the pretreated battery separator. It was measured that the weight of alumina in the alumina coating of the pretreated battery separator decreased by 18wt%.

[0056] Take an appropriate amount of the above-pretreated battery separator and HZSM-5 catalyst, mechanically mix them according to HZSM-5 / raw material = 8:1, and quickly pyrolyze them at 700°C for 14 minutes to obtain volatile components and solid carbon. The volatile components are condensed at 4°C to obtain a liquid product with a liquid product yield of 63.09%. The content of aromatics therein is analyzed by gas chromatography, and the yield of aromatics is calculated to be 60.14%. The pyrolyzed solid carbon is calcined at 500°C for 2 hours to obtain porous alumina. It was determined that the average particle size of the porous alumina is 37nm and the specific surface area is 284m 2 / g, pore volume is 0.748cm 3 / g.

[0057] Take an appropriate amount of the pretreated filtrate, add hydrogen peroxide to the filtrate, the weight ratio of the filtrate to hydrogen peroxide is 20:1, and stir until the solution is yellow-brown. Then control the polymerization stirring speed to 390r / min, the water bath temperature to 77°C, and the time to 3h. Then control the aging stirring speed to 350r / min, the water bath temperature to 75°C, and the time to 40h, and finally obtain liquid polyaluminum ferric sulfate.

[0058] Example 7

[0059] Take an appropriate amount of waste battery separator and immerse it in titanium dioxide waste acid at a solid-liquid ratio of 1:20 (g / mL), stir it at 90°C for 2h, then filter it, wash the filter residue with deionized water until it is neutral, and finally dry it at 109°C for 23h to obtain the filtrate and the pretreated battery separator. It was measured that the weight of alumina in the alumina coating of the pretreated battery separator decreased by 13wt%.

[0060] Take an appropriate amount of the above-pretreated battery separator and HZSM-5 catalyst, mechanically mix them according to HZSM-5 / raw material = 8:1, and quickly pyrolyze them at 650℃ for 15 minutes to obtain volatile components and solid carbon. The volatile components are condensed at 3℃ to obtain a liquid product with a liquid product yield of 60.89%. The content of aromatics therein is analyzed by gas chromatography, and the yield of aromatics is calculated to be 50.19%. The pyrolyzed solid carbon is calcined at 450℃ for 1h to obtain porous alumina. It was determined that the average particle size of the porous alumina is 57nm and the specific surface area is 213m 2 / g, pore volume is 0.309cm 3 / g.

[0061] Take an appropriate amount of the pretreated filtrate, add hydrogen peroxide to the filtrate, the weight ratio of the filtrate to hydrogen peroxide is 17:1, and stir until the solution is yellow-brown. Then control the polymerization stirring speed to 300r / min, the water bath temperature to 80°C, and the time to 3h. Then control the aging stirring speed to 300r / min, the water bath temperature to 70°C, and the time to 24h, and finally obtain liquid polyaluminum ferric sulfate.

[0062] Example 8

[0063] Take an appropriate amount of waste battery separator and immerse it in titanium dioxide waste acid at a solid-liquid ratio of 1:15 (gg / mL), stir it at 90°C for 2h, then filter it, wash the filter residue with deionized water until it is neutral, and finally dry it at 90°C for 12h to obtain the filtrate and the pretreated battery separator. It was measured that the weight of alumina in the alumina coating of the pretreated battery separator decreased by 34wt%.

[0064] Take an appropriate amount of the above-pretreated battery separator and HZSM-5 catalyst, mechanically mix them according to HZSM-5 / raw material = 10:1, and quickly pyrolyze them at 700℃ for 10 minutes to obtain volatile components and solid carbon. The volatile components are condensed at 1℃ to obtain a liquid product with a liquid product yield of 62.67%. The content of aromatics therein is analyzed by gas chromatography, and the yield of aromatics is calculated to be 55.32%. The pyrolyzed solid carbon is calcined at 420℃ for 2h to obtain porous alumina. It was determined that the average particle size of the porous alumina is 46nm and the specific surface area is 395m2 / g, pore volume is 0.614cm 3 / g.

[0065] Take an appropriate amount of the pretreated filtrate, add hydrogen peroxide to the filtrate, the weight ratio of the filtrate to hydrogen peroxide is 14:1, and stir until the solution is yellow-brown. Then control the polymerization stirring speed to 300r / min, the water bath temperature to 80°C, and the time to 3h. Then control the aging stirring speed to 300r / min, the water bath temperature to 80°C, and the time to 24h, and finally obtain liquid polyaluminum ferric sulfate.

[0066] Example 9

[0067] Take an appropriate amount of waste battery separator and immerse it in titanium dioxide waste acid at a solid-liquid ratio of 1:16 (g / mL), stir it at 110℃ for 2h, then filter it, wash the filter residue with deionized water until it is neutral, and finally dry it at 99℃ for 23h to obtain the filtrate and the pretreated battery separator. It was measured that the weight of alumina in the alumina coating of the pretreated battery separator decreased by 39wt%.

[0068] Take an appropriate amount of the above-pretreated battery separator and HZSM-5 catalyst, mechanically mix them according to HZSM-5 / raw material = 12:1, and quickly pyrolyze them at 650℃ for 12 minutes to obtain volatile components and solid carbon. The volatile components are condensed at 3℃ to obtain a liquid product with a liquid product yield of 66.25%. The content of aromatics therein is analyzed by gas chromatography, and the yield of aromatics is calculated to be 60.32%. The pyrolyzed solid carbon is calcined at 490℃ for 1h to obtain porous alumina. It was determined that the average particle size of the porous alumina is 55nm and the specific surface area is 263m 2 / g, pore volume is 0.546cm 3 / g.

[0069] Take an appropriate amount of the pretreated filtrate, add hydrogen peroxide to the filtrate, the weight ratio of the filtrate to hydrogen peroxide is 19:1, and stir until the solution is yellow-brown. Then control the polymerization stirring speed to 300r / min, the water bath temperature to 80°C, and the time to 2h. Then control the aging stirring speed to 300r / min, the water bath temperature to 75°C, and the time to 28h, and finally obtain liquid polyaluminum ferric sulfate.

[0070] Example 10

[0071] Take an appropriate amount of waste battery separator and immerse it in titanium dioxide waste acid at a solid-liquid ratio of 1:20 (g / mL), stir it at 110℃ for 5h, then filter it, wash the filter residue with deionized water until it is neutral, and finally dry it at 90℃ for 12h to obtain the filtrate and the pretreated battery separator. It was measured that the weight of alumina in the alumina coating of the pretreated battery separator decreased by 40wt%.

[0072] Take an appropriate amount of the above-mentioned pretreated battery separator and HZSM-5 catalyst, mechanically mix them according to HZSM-5 / raw material = 12:1, and quickly pyrolyze them at 700°C for 11 minutes to obtain volatile components and solid carbon. The volatile components are condensed at 2°C to obtain a liquid product with a liquid product yield of 68.23%. The content of aromatics therein is analyzed by gas chromatography, and the yield of aromatics is calculated to be 59.65%. The pyrolyzed solid carbon is calcined at 450°C for 2 hours to obtain porous alumina. It was determined that the average particle size of the porous alumina is 60nm and the specific surface area is 258m 2 / g, pore volume is 0.467cm 3 / g.

[0073] Take an appropriate amount of the pretreated filtrate, add hydrogen peroxide to the filtrate, the weight ratio of the filtrate to hydrogen peroxide is 10:1, and stir until the solution is yellow-brown. Then control the polymerization stirring speed to 340r / min, the water bath temperature to 80°C, and the time to 3h. Then control the aging stirring speed to 210r / min, the water bath temperature to 80°C, and the time to 24h, and finally obtain liquid polyaluminum ferric sulfate.

[0074] Comparative Example 1

[0075] The method of Example 1 is different in that titanium dioxide waste acid is not used, that is:

[0076] Take an appropriate amount of waste battery diaphragm and HZSM-5 catalyst, mix them mechanically according to HZSM-5 / raw material = 4:1, and quickly pyrolyze them at 500℃ for 20min to obtain volatile components and solid carbon. The volatile components are condensed at 0℃ to obtain liquid products, and the yield of liquid products is 31.42%. The content of aromatics in it is analyzed by gas chromatography, and the yield of aromatics is calculated to be 27.57%. The pyrolyzed solid carbon is calcined at 400℃ for 1h to obtain alumina. The average particle size of alumina is 27nm, and the specific surface area is 157m 2 / g, pore volume is 0.285cm 3 / g.

[0077] Comparative Example 2

[0078] The method of Example 1 is followed, except that the papermaking black liquor is replaced with water, that is:

[0079] Take an appropriate amount of waste battery separator and immerse it in water at a solid-liquid ratio of 1:20 (g / mL), stir it at 90°C for 2h, then filter it, wash the filter residue with deionized water until it is neutral, and finally dry it at 90°C for 12h to obtain the filtrate and the pretreated battery separator. It was measured that the weight of aluminum oxide in the aluminum oxide coating of the pretreated battery separator decreased by 0.1wt%.

[0080] Take an appropriate amount of the above-mentioned pretreated battery separator and HZSM-5 catalyst, mechanically mix them according to HZSM-5 / raw material = 4:1, and quickly pyrolyze them at 500°C for 20 minutes to obtain volatile components and solid carbon. The volatile components are condensed at 0°C to obtain a liquid product with a liquid product yield of 33.25%. The content of aromatics therein is analyzed by gas chromatography, and the yield of aromatics is calculated to be 28.84%. The pyrolyzed solid carbon is calcined at 400°C for 1 hour to obtain alumina. The average particle size of alumina is measured to be 28nm, and the specific surface area is 167m 2 / g, pore volume is 0.295cm 3 / g.

[0081] Test Case

[0082] The polyaluminium ferric sulfate liquid product prepared by the present invention is applied to domestic wastewater. The selected domestic wastewater is taken from a sewage treatment plant in Beijing. The water quality of the wastewater is shown in Table 1:

[0083] Table 1. Domestic sewage quality parameters

[0084] pH COD / (mg / L) Turbidity / NTU 7 245.87 235

[0085] Take 2 mL of the polyaluminium ferric sulfate solution in the above embodiment and comparative example 2, add it into 1 L of domestic wastewater, stir for 10 min and let it stand for a certain period of time, then take the supernatant to analyze the water quality. The results are shown in Table 2:

[0086] Table 2. Effect of water purifier on treating domestic sewage

[0087]

[0088]

[0089] It can be seen from the above table that the polyaluminium ferric sulfate prepared by the method of the present invention has a good effect on the removal of sewage turbidity and COD. Since the generated alum flowers are large and dense, their sedimentation time is relatively short.

[0090] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A method for high-value comprehensive utilization of waste battery separators, characterized in that: The following steps are involved: S1, mixing and filtering the waste battery separator and titanium dioxide waste acid to obtain a filtrate and a pretreated battery separator with a portion of the aluminum oxide coating removed; wherein the pretreated battery separator is subjected to catalytic pyrolysis to obtain aromatic hydrocarbons and solid carbon; S2, oxidizing, polymerizing and aging the filtrate in sequence to obtain polyaluminium ferric sulfate.

2. The method according to claim 1, characterized in that In S1, the amount of waste battery separator and titanium dioxide waste acid is such that the solid-liquid ratio is 1:10-20 g / mL; and / or, The mixing conditions include: temperature of 90 to 110° C. and time of 2 to 5 hours; Preferably, washing and drying are performed after said filtering; More preferably, the drying conditions include: a temperature of 80 to 120° C. and a time of 6 to 24 hours.

3. The method according to claim 1 or 2, characterized in that: The waste battery separator is a battery separator with an aluminum oxide coating.

4. The method according to any one of claims 1 to 3, characterized in that The weight of aluminum oxide in the pretreated battery separator is reduced by 10 to 40 wt % relative to the waste battery separator.

5. The method according to any one of claims 1 to 4, characterized in that The catalyst for catalytic pyrolysis is HZSM-5; and / or, The amount of catalyst used in the catalytic pyrolysis is catalyst: pretreated battery separator = 4 to 12:1; and / or, The conditions for the catalytic pyrolysis include: a temperature of 500 to 700° C. and a time of 10 to 20 minutes.

6. The method according to any one of claims 1 to 5, characterized in that In S1, after catalytic pyrolysis, volatile components are obtained and condensed to obtain aromatics.

7. The method according to any one of claims 1 to 6, characterized in that The oxidant used in the oxidation is hydrogen peroxide; and / or, The oxidation conditions included stirring until the solution was a yellow-brown color.

8. The method according to any one of claims 1 to 7, characterized in that The polymerization conditions include: temperature of 70-80° C., stirring speed of 200-400 r / min, and time of 2-5 h.

9. The method according to any one of claims 1 to 8, characterized in that The aging conditions include: reacting at a temperature of 70 to 80° C. and a stirring speed of 200 to 400 r / min for 24 to 48 hours.

10. The method according to any one of claims 1 to 9, characterized in that The solid carbon is roasted to obtain porous alumina; preferably, the roasting conditions include: a temperature of 400 to 500° C. and a time of 1 to 2 hours.

Citation Information

Cited By

  • Method for recycling polyolefin material from waste lithium battery

    CN120424675A